Brookers environmental legislation handbook 2014 : with an introduction - Warnock, Ceri; Wheen, Nicola R. (Nicola Rowan); Brooker's (Firm) (Wellington [N.Z.] : Thomson Reuters New Zealand, 2014)
Brookers environmental legislation handbook 2014 brings together extracts of the essential environmental legislation in one convenient, accessible volume for students, academics, practitioners, planners and local authories.
Conservation/heritage -- Wildlife -- Oceans -- Minerals -- Hazards/Pollutants -- Institutions.
Keywords: New Zealand; Conservation of natural resources -- New Zealand -- Management